Dysregulated Circulating Dendritic Cell Function in Ulcerative Colitis Is Partially Restored by Probiotic Strain Lactobacillus casei Shirota. (18th July 2013) - Mann, Elizabeth R.; You, Jialu; Horneffer-van der Sluis, Verena; Bernardo, David; Omar Al-Hassi, Hafid; Landy, Jon; Peake, Simon T.; Thomas, Linda V.; Tee, Cheng T.; Lee, Gui Han; Hart, Ailsa L.; Yaqoob, Parveen; et al.
Abstract : Background . Dendritic cells regulate immune responses to microbial products and play a key role in ulcerative colitis (UC) pathology. We determined the immunomodulatory effects of probiotic strain Lactobacillus casei Shirota (LcS) on human DC from healthy controls and active UC patients. Methods . Human blood DC from healthy controls (control-DC) and UC patients (UC-DC) were conditioned with heat-killed LcS and used to stimulate allogeneic T cells in a 5-day mixed leucocyte reaction. Results . UC-DC displayed a reduced stimulatory capacity for T cells (P < 0 . 05 ) and enhanced expression of skin-homing markers CLA and CCR4 on stimulated T cells (P < 0 . 05 ) that were negative for gut-homing marker β 7. LcS treatment restored the stimulatory capacity of UC-DC, reflecting that of control-DC. LcS treatment conditioned control-DC to induce CLA on T cells in conjunction with β 7, generating a multihoming profile, but had no effects on UC-DC. Finally, LcS treatment enhanced DC ability to induce TGFβ production by T cells in controls but not UC patients. Conclusions . We demonstrate a systemic, dysregulated DC function in UC that may account for the propensity of UC patients to develop cutaneous manifestations. LcS has multifunctional immunoregulatory activities depending on the inflammatory state; therapeutic effects reported in UC may be due to promotion of homeostasis.